The use of innervated radial artery superficial palmar branch perforator free flap for complex digital injuries reconstruction. Issue 2 (4th March 2018) - Chi, Zhenglin; Pafitanis, Georgios; Pont, Luis Eduardo Parra; Vijayan, Roshan; Marcelli, Stefano; Gao, Weiyang; Li, Zan; Zhou, Xiao; Song, Dajiang; Yang, Peng
Abstract: Loco-regional flaps have been widely used for the reconstruction of digital injuries without requiring microvascular anastomosis, however, they result in scarring and compromised functional outcomes. This study demonstrates our experience utilizing the innervated radial artery superficial palmar branch (RASPB) perforator free flap for complex digital injury reconstruction. From May 2007 to March 2014, the innervated RASPB perforator free flap was used to reconstruct 79 distal complex hand and digital soft tissue defects of which 14 were used to re-vascularise the distal digit in a flow-through fashion. All free flaps were innervated by the palmar cutaneous branch of the median nerve. All 79 free flaps survived and all 14 digits re-vascularized successfully. One flow-through free flap developed distal skin necrosis which healed uneventfully without further procedure. The average follow-up was 21.5 months. Measurement of two-point discrimination ranged from 7 to 13 mm. All patients were satisfied with the aesthetic results. The innervated RASPB perforator free flap is a feasible and effective option for the reconstruction of complex digital defects and the flow-through concept, when utilized in cases with compromised vascularity, provides reliable re-vascularization. Level III, therapeutic study.